Mean Platelet Volume in Ocular Behçet’s Disease - Fatih Mehmet Türkcü; Abdullah Kürşat Cingü; Harun Yüksel; Yasin Çınar; Meltem Akkurt; Muhammed Şahin; Zeynep Özkurt; Alparslan Şahin; İhsan Çaça (The Scientific World Journal)
Objective. To determine whether mean platelet volume (MPV) is an indicator of disease severity in ocular Behçet’s Disease (BD). Materials and Methods. The study population was 30 newly diagnosed ocular BD patients who presented with active uveitis. These patients had no past history of smoking, drug use, or systemic diseases including diabetes mellitus, hypertension, cardiovascular disease, and renal disease. A control group consisting of 34 healthy individuals was included for comparison. MPV measurements were performed serially upon presentation with active uveitis and at one and three month thereafter in BD group whereas only at presentation in the controls. Results. Upon presentation with active uveitis, the mean MPV levels were 7.88 ± 1.14 femtoliters (fL) for BD group. During the posttreatment follow-up period at first and third months, BD patients demonstrated a mean MPV level of 7.71 ± 1.12 fL and 7.65 ± 1.04 fL, respectively. The mean MPV value of control group, was 8.39 ± 0.66 fL at presentation. Fluctuations in MPV values were not significant in the BD group, while there was a significant difference between the initial measurements of the BD and control groups. Conclusion. MPV measurement in ocular BD is not a predictive laboratory test to determine the clinical improvement in early stages following classical immunosuppressive treatment.